Exploring the potential effect and mechanisms of protocatechuic acid on human hair follicle melanocytes - Li Bo; Tan Jun; Zou Bosheng; Liu Xiaojia; Yu Yiling (Acta Pharmaceutica)
This study aims to evaluate the effect of protocatechuic acid (PCA) on human hair follicle melanocytes (HFM). Normal primary HFM were isolated and cultured till logarithmic period of second passage, then treated with different concentrations of PCA (0.1–200 μmol L−1) to study the cell proliferation, melanin contents, tyrosinase activity and protein and mRNA expression of melanogenic genes (tyrosinase-related protein 1 (TRP-1), tyrosinase-related protein 2 (TRP-2), and microphthalmia-associated transcription factor (MITF)) in the cultured HFM. In addition, we have also measured the contents of superoxide dismutase (SOD) and glutathione (GSH) in PCA treated HFM. Vitamin C was used as a positive control. The result showed that PCA can decrease the synthesis of melanin and the tyrosinase activity with IC50 = 8.9 μmol L−1 and IC50 = 6.4 μmol L−1, respectively, at the treatment time of 24 hours, without inducing any cytotoxicity in HFM cells. In addition, the mRNA transcription and protein expression levels of TRP-1, TRP-2 and MITF significantly decreased with a dose-dependent manner after 24-hour PCA treated in HFM cells. Furthermore, PCA has significantly increased the SOD and GSH activity in a dose-dependent manner for 24-hour PCA treatment. This study suggested that PCA has an inhibitory effect on the production of melanin through down-regulation of the expression of melanogenesis-related protein and the effect of anti-oxidation, which could be useful for the therapy of melanin overproduction or skin whitening.